HOBBES’ ACCOUNT OF LIFE IN THE STATE OF NATURE AND ITS IMPLICATIONS - Matić, Ivan (Srpska politička misao, 2025)
In an infamous paragraph in his magnum opus, Leviathan, Thomas Hobbes describes what he perceives to be the miserable condition of humankind in the state of nature, concluding that human life in this state is “solitary, poor, nasty, brutish, and short” (Hobbes 1996, 84). To properly understand the relevance and implications of this claim, we shall first examine how the concept of a state of nature came to be. Then, we shall look at the specificities of Hobbes’ own account, pointing out certain generally neglected details. Afterward, we will analyze what some of Hobbes’ critics had to say on the issue, and how he either pre-emptively defended his claims or could have responded to them, based on his theory. Finally, we shall examine what might be the most complex and intriguing topic related to this subject: namely, how a defense of natural rights as inalienable could be constructed upon a foundation of a chaotic state of nature driven by scarcity and conflict.